Design a Framework on Teaching Experimental Practice Competencies in Primary Science Education - Thi Phuong Dung, Tran; Thuy Xuan Thao, Trinh; Vinh, Truong; Luu Tang Phuc, Khang (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2024)
This research offers a detailed framework for evaluating the assessing the teaching experiment practice of teachers in science education, specifically within the primary stage of the Vietnamese educational system. The framework development employs sophisticated statistical methods, such as first- and second-order confirmatory factor analysis (CFA), to guarantee a rigorous psychometric evaluation. The approach includes three competence factors: professional knowledge, practical skills, and the capacity to arrange instruction and evaluation. The research findings indicate that the proposed measure satisfies the requirements for internal consistency, reliability, and validity, serving as a helpful instrument for evaluating instructors' teaching practices in scientific education. The study's thorough psychometric assessment enhances the comprehension of experimental practice abilities within the Vietnamese educational sector. The results have ramifications that extend beyond the Vietnamese context and are pertinent to international education. In addition, the study enriches the understanding of measuring teaching experiment practice competencies in the context of science education, providing valuable insights for educators and motivating them in Vietnam and other countries.